Immuno-oncology: Allying forces of radio- and immuno-therapy to enhance cancer cell killing. (December 2016) - Bernier, Jacques
Abstract: Besides the local effects of ionizing radiation at the cellular and molecular levels in tumor tissues, the interactions of radiotherapy with the host's immune system are nowadays at the center of many investigations. In some cases, these interactions can be strong enough to immunize the patient against the tumor, leading to a rejection by the host of both the irradiated tumor and distant metastases. In this latter case, the rejection mechanism is called "abscopal effect". Over the last two decades, increasing attention has also been paid to the combination of various forms of immunotherapies with radiation, as an attempt to boost cancer cell killing mechanisms. In particular, a significant number of translational and clinical studies are now investigating both the effects of immune checkpoint blockade strategies and adoptive immunotherapies in combination with radiation. A better understanding of the mechanisms driving the interactions between ionizing radiation and the immune system help us envision the advantages that may be offered by the adjunction of immunotherapy to radiotherapy in various clinical models.